Analysis of high level swim performance in relationship with the introduction of new race swimsuits - Falcone, I.; Nagni, G.; Demarie, S. (Sport Science Review, 2010)
The aim of this study was to investigate the trend of high level swim performance in the last twenty years to observe the results of the introduction of new kinds of race swimsuits on performance. Two kinds of suits were considered, those with more percentage of body coverage used since 2000, and the polyurethane swimsuits, introduced at the beginning of 2008. Winners' times in short and long course F.I.N.A. World Championship and Olympic Games from 1991 to 2009 were analyzed. Times of long course World Championships and Olympic Games were brought together and compared to see if any difference resulted. World records' trend was analyzed from the '80s to the end of 2009, even to see gender's differences. Finally, access times to Olympic finals and mean times performed in these races were recorded. Data were taken from official timing websites. The analysis shows that the swimsuits strongly determined the performances during the last twenty years. Great improvement was noticed in correspondence with the introduction of the two kinds of swimsuits in all the different analysis performed, with no gender's differences. The extent of this improvement is more evident for the suits with polyurethane technology and regards all the swim specialties.